Development of an Innovative Meta-Panel Sandwich Core for Structure Protection against Blast and Impact Loads - Vo, Hoang Nhi (Curtin University, 2022)
This research develops a novel protective structure named “meta-panel” for mitigation of blast/impact loading. The proposed meta-structure consists of local resonators which convert and trap blast/impact energy to kinetic energy through local vibrations of the resonators, hence reducing the loading energy transmission to the protected structures. This design opens a door for a new approach to structural protections from the traditional means of either strengthening and/or energy absorption through large plastic deformations of sacrificial structures.